Diseminasi Pengayaan Kosakata (Pusat Pengembangan Dan Perlindungan, Badan Pengembangan Dan Pembinaan Bahasa Kementerian P&K Republik Indonesia) - Sri Widyastuti; Sri Ambarwati; Herlan (SULUH: Jurnal Abdimas, 2019)
Indonesian is the language of unity in Indonesia in accordance with Article 36 of the 1945 Constitution which states that the State Language is Indonesian. In line with the development of time the Indonesian language has changed from time to time the Language Development and Development Agency of the Ministry of Education and Culture in charge of socializing about the Vocabulary Enrichment Dissemination program. In connection with the foregoing, the Language Development and Development Agency of the Ministry of Education and Culture held a Dissemination of Indonesian Language Vocabulary Enrichment Program at the Faculty of Economics and Business, Pancasila University (FEB-UP).